A Major Scottish Tramp Ship and Cargo Liner Company: Andrew Weir’s Bank Line-1875-2016. Part 1, 1875-1970 - Fenton, Roy; Murphy, Hugh (The Northern Mariner / Le marin du nord, 2025)
This article in two parts, the first from 1885 to 1970 and the second from 1970 to 2016 covers the history of a major Scottish tramp ship and cargo liner company, Andrew Weir’s Bank Line through the era of sail and steam and the early adoption of the motor ship in the interwar period and beyond to an all-motor ship fleet. Beginning as a tramp sailing ship venture, Bank Line is notable in that it also embraced liner shipping relatively early in its existence. This dual character, plus early enthusiasm for motor vessels and oil tankers in tandem with family ownership, sets it apart from many British shipping firms and makes it worthy of extended study. We also cover the many associated companies of Bank Line’s parent company, Andrew Weir Ltd., to give the reader a fuller perspective of where Bank Line stood relative to it. Owing to the paucity of extant records, we cover the financial aspects of the company during the Second World War and from the late 1970s onwards up to the renaming of the company as Andrew Weir Shipping Ltd. in 1988 to dissolved company status in 2016.